Investigation of using the ceramic polishing brick powder in engineered cementitious composites. (November 2021) - Xiong, Yan; Xu, Guozhong; Wu, Di; Fang, Shuai; Tang, Yingfeng
Abstract: With the development of the ceramic industry and the renovation of old buildings, ceramic waste is increasing dramatically in the process of production. Among ceramic wastes, ceramic polishing brick powder (CPBP) has high hardness and a large amount of silicate minerals, which endow it with a good skeleton and pozzolanic activity. Therefore, reasonable recycling of CPBP has important environmental protection and economic values. This study used CPBP as a supplementary cementing material to replace fly ash in engineered cementitious composites (ECCs). The basic characteristics of CPBP were characterized by an activity index test and micro analysis for comparison with fly ash. Prior to the uniaxial tensile test of the newly designed ECC, an axial compression test, X-ray diffraction (XRD), and mercury intrusion porosimetry (MIP) of cement quartz mortar (CQM) were conducted to evaluate the feasibility of replacing fly ash with CPBP in ECCs. The test results show that the fineness of CPBP is between that of cement and fly ash, and that CPBP particles have a smoother surface than cement particles. The 7-day activity index of CPBP was the same as that of fly ash, while the 28-day activity index of CPBP was 14.29% higher. When the CPBP content is 35% of the cementitious material, the compressive and tensile strengths of CQM are maximized. The addition of CPBP significantly decreased the porosity and achieved pore structure refinement of CQM. When CPBP replaces half or all fly ash, the newly designed ECC can achieve good tensile properties. Moreover, by replacing fly ash with CPBP at 35% of the cementitious material, the designed ECC specimen showed a better tensile strength (5.89 MPa) and ultimate tensile strain capacity (4.39%). Therefore, it has great engineering application prospects. Highlights: A new type of ECC is designed by adding CPBP as a supplementary cementing material. The 28-day activity index of CPBP is higher than that of fly ash. The ECC specimens containing CPBP achieve at least 4% ultimate tensile strain.